Stabilization of three-dimensional charge order through interplanar orbital hybridization in PrxY1-xBa2Cu3O6+δ - Ruiz, Alejandro; Gunn, Brandon; Lu, Yi; Sasmal, Kalyan; Moir, Camilla M.; Basak, Rourav; Huang, Hai; Lee, Jun-Sik; Rodolakis, Fanny; Boyle, Timothy J.; Walker, Morgan; He, Yu; et al. (Arxiv, 2022)
The shape of 3d-orbitals often governs the electronic and magnetic properties of correlated transition metal oxides. In the superconducting cuprates, the planar confinement of the dx2−y2 orbital dictates the two-dimensional nature of the unconventional superconductivity and a competing charge order. Achieving orbital-specific control of the electronic structure to allow coupling pathways across adjacent planes would enable direct assessment of the role of dimensionality in the intertwined orders. Using Cu-L3 and Pr-M5 resonant x-ray scattering and first principles calculations, we report a highly correlated three-dimensional charge order in Pr-substituted YBa2Cu3O7, where the Pr f -electrons create a direct orbital bridge between CuO2 planes. With this we demonstrate that interplanar orbital engineering can be used to surgically control electronic phases in correlated oxides and other layered materials.